Análise estrutural em elementos finitos de escadas autoportantes - Silva, Joefferson Abrão Pereira (Universidade Federal Rural do Semi-Árido, 2017)
Stairs are indispensable structural elements in buildings that includes more than one floor, it gives the possibility to exchange from the different heights of slabs with the least possible effort, preserving the aesthetics and safety. These structures are designed and classified between the most varied types, shapes and dimensions, depending on the space available, traffic of people and the architectural aspects. Among these various models, the self-supporting stairs do not present support on its landing level, this structure classifies into the group of special stairs, as they do not behave as conventional models, they need a specialized treatment of analysis. In this manner, this work aimed at the development of a simple analytical model for the structural analysis of self - supporting ladders. The analysis of the three-dimensional model was performed using the Finite Element Method, extracting parameters for the development of the analytical model. Then, it was executed an investigation of the literal model through use of Virtual Works Principle as well as it was determined an equation that describes the displacement of the structure at its most critical point. Therefore, it was made possible to conclude that is the three-dimensional model of the self-supporting ladder with no level support can be described by a corrected simple plan model.
Keywords: Escadas autoportantes; estudo comparativo; análise estrutural; self-supporting stairs; comparative study; structural analysis; ENGENHARIAS::ENGENHARIA CIVIL